Ugonin J Acts as a SARS-CoV-2 3C-like Protease Inhibitor and Exhibits Anti-inflammatory Properties - Chiou, Wei-Chung; Lu, Hsu-Feng; Hsu, Nung-Yu; Chang, Tein-Yao; Chin, Yuan-Fan; Liu, Ping-Cheng; Lo, Jir-Mehng; Wu, Yeh B; Yang, Jinn-Moon; Huang, Cheng (Frontiers in Pharmacology, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection causes severe ‘flu-like’ symptoms that can progress to acute respiratory distress syndrome (ARDS), pneumonia, renal failure, and death. From the therapeutic perspective, 3-chymotrypsin-like protein (3CLpro) is a plausible target for direct-acting antiviral agents because of its indispensable role in viral replication. The flavonoid ugonin J (UJ) has been reported to have antioxidative and anti-inflammatory activities. However, the potential of UJ as an antiviral agent remains unexplored. In this study, we investigated the therapeutic activity of UJ against SARS-CoV-2 infection. Importantly, UJ has a distinct inhibitory activity against SARS-CoV-2 3CLpro, compared to luteolin, kaempferol, and isokaempferide. Specifically, UJ blocks the active site of SARS-CoV-2 3CLpro by forming hydrogen bonding and van der Waals interactions with H163, M165 and E166, G143 and C145, Q189, and P168 in subsites S1, S1', S2, and S4, respectively. In addition, UJ forms strong, stable interactions with core pharmacophore anchors of SARS-CoV-2 3CLpro in a computational model. UJ shows consistent anti-inflammatory activity in inflamed human alveolar basal epithelial A549 cells. Furthermore, UJ has a 50% cytotoxic concentration (CC50) and a 50% effective concentration (EC50) values of about 783 and 2.38 µM, respectively, with a selective index (SI) value of 329, in SARS-CoV-2-infected Vero E6 cells. Taken together, UJ is a direct-acting antiviral that obstructs the activity of a fundamental protease of SARS-CoV-2, offering the therapeutic potential for SARS-CoV-2 infection.